2008
DOI: 10.1002/cne.21514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the distributions of urocortin‐containing and cholinergic neurons in the perioculomotor midbrain of the cat and macaque

Abstract: Urocortin is a novel neurotransmitter that appears to play a role in eating and drinking behavior. Most urocortin-positive (urocortin(+)) neurons in rodents are found in the cytoarchitecturally defined Edinger-Westphal nucleus (EW). However, the EW is traditionally described as the source of the preganglionic parasympathetic outflow to the ciliary ganglion. We examined the distribution of urocortin(+) cells and motoneurons by use of immunohistochemical staining for this peptide and for choline acetyltransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 83 publications
(102 reference statements)
8
90
1
1
Order By: Relevance
“…In monkey, the Edinger-Westphal nucleus contains choline acetyltransferase-positive, presumed pre-ganglionic neurons of the ciliary ganglion whereas the human Edinger-Westphal consists of noncholingeric urocortin-positive neurons (Horn et al, 2008). We found that the anatomical distribution of the midbrain CART neurons in the monkey is identical to that of the midbrain urocortins-1 neurons as recently described (May et al, 2008). Hence in monkey, midbrain CART neurons are located between the Edinger-Westphal nucleus and the occulomotor (III) nucleus.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In monkey, the Edinger-Westphal nucleus contains choline acetyltransferase-positive, presumed pre-ganglionic neurons of the ciliary ganglion whereas the human Edinger-Westphal consists of noncholingeric urocortin-positive neurons (Horn et al, 2008). We found that the anatomical distribution of the midbrain CART neurons in the monkey is identical to that of the midbrain urocortins-1 neurons as recently described (May et al, 2008). Hence in monkey, midbrain CART neurons are located between the Edinger-Westphal nucleus and the occulomotor (III) nucleus.…”
Section: Introductionsupporting
confidence: 82%
“…A diagram showing the relative positions of the periaquaductal gray (PAG), Edinger-Westphal nuclei (EW), the occulomotor nuclei (III) and the CART neurons (dots) is shown below the montages. The area where the CART positive neurons are located has been referred to as the supraocculomotor area, or SOA (May et al, 2008). The montages were built automatically by Slidebook 4.2 and the stereology microscope.…”
Section: -Hormone Assaysmentioning
confidence: 99%
“…Sections were then incubated for 48 h in primary antibody to UCN1 (U4757; Sigma) or CRF (gift of Wylie Vale; Salk Institute, La Jolla, Calif., USA). These antibodies have been extensively characterized and previously applied to primate brain [37,38,39]. The UCN1 antibody was diluted 1/15,000 in 0.6% normal goat serum, 0.02 M KPBS and 0.4% Triton.…”
Section: Methodsmentioning
confidence: 99%
“…In order to better determine the true identity of EW, we recently investigated the populations of neurons found in the vicinity of the oculomotor nucleus, the perioculomotor (pIII) populations, in the cat and monkey (May et al, 2008). Specifically, we compared the locations of the cholinergic and urocortin peptidergic populations by using antibodies to choline acetyl transferase (ChAT) and urocortin I.…”
Section: Introductionmentioning
confidence: 99%